Surface degradation of lithium disilicate ceramic after immersion in acid and fluoride solutions - Vechiato-Filho, Aljomar Jose [UNESP]; Dos Santos, Daniela Micheline [UNESP]; Goiato, Marcelo Coelho [UNESP]; Moreno, Amalia [UNESP]; De Medeiros, Rodrigo Antonio [UNESP]; Kina, Sidney; Rangel, Elidiane Cipriano [UNESP]; DA Cruz, Nilson Cristino [UNESP] (My University, 2015)
Purpose: To analyze whether immersion in sodium fluoride (NaF) solutions and/or common acidic beverages (test solutions) would affect the surface roughness or topography of lithium disilicate ceramic. Methods: 220 ceramic discs were divided into four groups, each of which was subdivided into five subgroups (n = 11). Control group discs were immersed in one of four test beverages for 4 hours daily or in artificial saliva for 21 days. Discs in the experimental groups were continuously immersed in 0.05% NaF, 0.2% NaF, or 1.23% acidulated phosphate fluoride (APF) gel for 12, 73, and 48 hours, respectively, followed by immersion in one of the four test beverages or artificial saliva. Vickers microhardness, surface roughness, scanning electron microscopy (SEM) associated with energy dispersive spectroscopy, and atomic force microscopy (AFM) assessments were made. Data were analyzed by nested analysis of variance (ANOVA) and Tukey's test (a = 0.05). Results: Immersion in the test solutions diminished the microhardness and increased the surface roughness of the discs. The test beverages promoted a significant reduction in the Vickers microhardness in the 0.05% and 0.2% NaF groups. The highest surface roughness results were observed in the 0.2% NaF and 1.23% APF groups, with similar findings by SEM and AFM. Acidic beverages affected the surface topography of lithium disilicate ceramic. Fluoride treatments may render the ceramic surface more susceptible to the chelating effect of acidic solutions.